Multiple GCD genes required for repression of GCN4, a transcriptional activator of amino acid biosynthetic genes in Saccharomyces cerevisiae. - Harashima, S (1986)
GCN4 encodes a positive regulator of multiple unlinked genes encoding amino acid biosynthetic enzymes in Saccharomyces cerevisiae. Expression of GCN4 is coupled to amino acid availability by a control mechanism involving GCD1 as a negative effector and GCN1, GCN2, and GCN3 as positive effectors of GCN4 expression. We used reversion of a gcn2 gcn3 double mutation to isolate new alleles of GCD1 and mutations in four additional GCD genes which we designate GCD10, GCD11, GCD12, and GCD13. All of the mutations lead to constitutive derepression of HIS4 transcription in the absence of the GCN2+ and GCN3+ alleles. By contrast, the gcd mutations require the wild-type GCN4 allele for their derepressing effect, suggesting that each acts by influencing the level of GCN4 activity in the cell. Consistent with this interpretation, mutations in each GCD gene lead to constitutive derepression of a GCN4::lacZ gene fusion. Thus, at least five gene products are required to maintain the normal repressed level of GCN4 expression in nonstarvation conditions. Interestingly, the gcd mutations are pleiotropic and also affect growth rate in nonstarvation conditions. In addition, certain alleles lead to a loss of M double-stranded RNA required for the killer phenotype. This pleiotropy suggests that the GCD gene products contribute to an essential cellular function, in addition to, or in conjunction with, their role in GCN4 regulation.